DIGITAL TRANSFORMATION IN MSME BOOKKEEPING SYSTEM: IMPACTS ON ACCURACY AND FINANCIAL DECISION-MAKING - Sartono, Sartono; Kriatiawati, Endang; Setiawan, Aris (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
MSMEs in Indonesia now need to undergo digital transformation to increase their operational efficiency and competitiveness. Inaccurate accounting frequently results in poor financial choices, which might put the company's survival at risk. This study seeks to investigate how digital transformation in bookkeeping systems can enhance the correctness of financial data and aid MSMEs in making better financial decisions. To explore the links between variables, a quantitative research method using SEM was utilized. Random sampling was the sampling method utilized, with a population of 164,364 MSMEs in West Kalimantan Province. With a 0.05 significance level, the Isaac and Michael formula was used to calculate the minimum sample size, which came out to be 140. But this study included 250 MSMEs in total to guarantee data reliability and representativeness. According to the data, digital literacy and transformation have a beneficial and substantial impact on the correctness of bookkeeping. The connection between digital transformation and bookkeeping accuracy is not, however, moderated by digital literacy. In addition, the data show that the accuracy of bookkeeping greatly impacts the caliber of financial choices made by MSMEs. This study contributes by demonstrating that digital transformation improves bookkeeping accuracy independently of digital literacy levels, highlighting the usability of digital accounting systems in low-skill environments.